The impact of dietary compliance on diabetic foot ulcer healing: A cross-sectional study - Dadi Santoso; Rajesh Kumar Muniandy; Putra Agina Widyaswara Suwaryo (Penerbit USIM, 2025)
Diabetic foot ulcers (DFUs) are a major complication of diabetes mellitus and are influenced by various factors, including dietary behavior. Proper diet adherence is essential for glycemic control and tissue regeneration, yet its role in ulcer healing remains underexplored. This cross-sectional study involved 100 type 2 diabetes mellitus patients with DFUs receiving home-based care in a community setting. Dietary compliance was measured using a structured questionnaire based on the 3J principle (meal timing, type, and portion). Ulcer healing was evaluated using the Wagner grading system. Data were analyzed using chi-square and logistic regression tests with SPSS 25.0. Among patients with high dietary compliance, 73.3% showed significant ulcer healing, compared to 42.5% in the low compliance group (p = 0.008). Dietary compliance was a significant predictor of ulcer healing (OR = 3.18; 95% CI = 1.41–7.15). Higher dietary compliance was associated with better short-term diabetic ulcer healing. While integrating nutrition education into home care services may be a valuable component of DFU management, our findings cannot confirm its independent effect, and further prospective research is warranted to determine causality and underlying mechanisms.